The Effect of The ERACS Method on The Acceleration of Mobilization of Post Sectio Caesaria Patients at Academic Hospital Universitas Gadjah Mada In 2023 - Krismayanti, Dewi; Haspitaningrum, Anjarsari; Risanto, Esti Utami (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
Background: ERACS (Enhanced Recovery After Caesarian Surgery) is a fast programrecovery after a Caesarean section in the form of a series of care starting from preoperativepreparation, intraoperative and post-operative care until the patient is discharged. InIndonesia itself, the implementation of the ERACS protocol began to be implemented in2019. UGM Academic Hospital, the ERACS method is still a new service from the MaternalPerinatal Installation and will start running in November 2022. This research aims todetermine the difference in maternal mobilization time post Sectio Caesaria with the ERACSmethod and mobilization of mothers post non-eracs SC at UGM Academic Hospital in 2023.This research is a quantitative research using a quasi-experimental method with anonequivalent posttest control group design. The research was conducted at the UGMAcademic Hospital in April - September 2023. The sampling technique was accidentalsampling. The research results showed that the average mobilization of post-Sc patientsusing the ERACS method was 13.1 hours and the average mobilization of non-ERACS post-Scpatients was 33.7 hours. From the results of the analysis of 54 respondents using theIndependent Sample Test, it shows a value of 0.000. So H0 is rejected and Ha is accepted.Conclusion: there is an effect of giving the ERACS method by accelerating the mobilizationof women giving birth post sc.Keywords: Sectio Caesaria, Maternity, Mobilization, Rapid Mobilization, ERACS